Continuing training from the perspective of professional collaboration between teachers - Silva, Michelly Vital da (2022)
This article presents study data whose objective was to review the state of the question regarding continuing education in the perspective of professional collaboration between teachers. The interest in the theme stems from the specialized literature pointing out that the continuing education offered through courses, lectures and seminars has been insufficient to meet the needs of teachers in the face of the current challenges of the profession, showing the convenience of knowing more effective alternatives. Recent empirical in-service training was searched using the descriptor of recent empirical research produced in the last five years and published in the database of the Brazilian Digital Library of Theses and Dissertations, BDTD, Capes Periodical Portal and in the scientific data portal WorldWideScience.org. The results found show that continuing education processes, carried out in a collaborative way between teachers, promote changes in pedagogical practice and contribute to the professional development of teachers.